Computational weld mechanics : Towards simplified and cost effective FE simulations - Bhatti, Ayjwat Awais (KTH, Lättkonstruktioner, 2015)
It is the demand of the world’s ever increasing energy crisis to reduce fuel consumption wherever possible. One way of meeting this demand is by reducing the weight of a structure by replacing thick plates of low strength steel with thin plates of high strength steel in the structure. Fusion welding process is extensively used in the manufacturing industry, however, despite many advantages different problems such as weld defects, residual stresses and permanent distortions are associated with this process. Finite element (FE) method has proved itself as an alternative and acceptable tool for prediction of welding residual stresses and distortions. However, the highly nonlinear and transient nature of the welding process makes the FE simulation computationally intensive and complex. Thus, simplified and efficient welding simulations are required so that they can be applied to industrial scale problems. In this research work an alternative FE simulation approach for the assessment of welding residual stresses, called rapid dumping is developed. This approach proved to be efficient and predicted the residual stress with acceptable accuracy for different small scale welded joints. This approach was further implemented on a large scale welded structures along with other available approaches. It was found that the computational time involved in the welding simulations for large structures using rapid dumping approach can be reduced but at the cost of accuracy of the results. Furthermore, influence of thermo-mechanical material properties of different steel grades (S355-S960) on welding residual stresses and angular distortion in T-fillet joints is investigated. It is observed that for assessment of residual stresses, except yield stress, all of the thermo-mechanical properties can be considered as constant. For the prediction of angular distortions with acceptable accuracy, heat capacity, yield stress and thermal expansion should be employed as temperature dependent in the welding simulations. Finally, the influence of two different LTT (Low Transformation Temperature) weld filler material on residual stress state and fatigue strength was investigated. It was observed that a reduction in tensile residual stresses at the weld toe of the joint was observed. Furthermore, at higher R-ratio no significant increase in the fatigue strength was observed . However, at low R-ratio significant  increase in fatigue strength was observed. === QC 20150529